Enabling and constraining causal powers for research and innovation in the South African higher education - Monnapula-Mapesela, M. (South African Journal of Higher Education, 2024)
This article highlights the critical importance of research and innovation in higher education, using South Africa (SA) as a case study. It analyses discourses that enable and constrain research and innovation. Margaret Archer’s social realist theory and stratified construct of structure, culture and agency is employed to understand various emerging transformation discourses exerting enabling or constraining causal powers for research and innovation. The interplay between structural, cultural, and agential milieus is investigated to better understand the urgency towards research and innovation. With this understanding, academics might locate their agency in the global and local contexts, create ideal conditions and build corporate agency for strengthening research and innovation. Universities with limited resources, should not reinvent what already exists, but should responsibly borrow key aspects that would thrive in their own contexts. However, it must be cautioned that no system of the world can exist as an end without deficits and flaws.